The Spectrum of Pulmonary Disease in Patients with HIV Infection - Julio Sg Montaner; Leila Spour; Carlos Zala (Canadian Journal of Infectious Diseases)
Pneumocystis carinii pneumonia (PCP) and Kaposi’s sarcoma were the harbingers of the HIV epidemic more than 10 years ago. Since then. the spectrum of pulmonary disease associated with HIV infection has become better understood. Although most of these conditions are infectious in nature. neoplastic and inflammatory processes also occur with increased frequency. The most common infectious pulmonary diseases include PCP. Mycobacterium tuberculosis infection and pyogenic bacterial pneumonia secondary to Streptococcus pneumoniae. Haemophilus influenzae or Staphylococcus aureus. Among the noninfectious causes of pulmonary disease. the most common are Kaposi's sarcoma. airways hyper-reactive disease (asthma) and emphysema. Respiratory involvement in HIV-infected individuals is not always related to the HIV infection. These patients often present with pulmonary disorders that are common in the genernal population. Differential diagnosis of respiratory conditions is significantly facilitated by the prior knowledge of the degree of immunodeficiency present as measured by the CD4 count. In particular, most episodes of PCP occur in patients with absolute CD4 counts below 200 cells/mm3. On the other hand. bacterial pneumonias and tuberculosis tend to occur at any time during the natural history of HIV disease. History and physical examination can help in the differential diagnosis; however. they are rclatively nonspecific in this setting. The same can be said of radiographic findings as well as laboratory and physiological abnormalities. Of note, the lactate dehydrogenase (LDH) serum level has proved to be extremely useful in ruling out PCP. Even mild PCP is usually accompanied by a significant elevation of LDH. Furthermore, the degree of LDH elevalion generally correlates wilh the severity of the PCP episode. Also, changes in LDH parallel the clinical course of the underlying PCP. Often LDH level has been useful in discriminating worsening PCP following the initiation of therapy from worsening respiratory symptoms due to superimposed disease. It must be emphasized, however. thal LDH level. although a very sensitive marker for PCP. is also nonspecific. Of note, hemolysis, lymphomas, pulmonary embolism, liver disease and dapsone therapy can be associated with elevated LDH in the context of HIV disease. Given the high frequency of respiratory involvement in this patient populalion. it is generally recommended thal preventive therapies be used whenever possible. Current recommendations stress the need for pneumococcal vaccine, yearly flu vaccination and routine screening with tuberculin skin test (PPD). HIV-infected individuals with a PPD skin test reaction of 5 mm of induration or greater using 5 tuberculin units will be considered candidates for one year of isoniazid prophylaxis. PCP prophylaxis has been shown to be extremely useful in this selling either as primary or secondary prophylaxis. Recently. rifabutin at doses of 300 mg daily has been shown to decrease significantly the frequency of Mycobacterium avium complex infection in patients with CD4 counts below 100/mm3 . (Pour résumé. voir page 35E)